2012
DOI: 10.1159/000339750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidafenacin on Nocturia and Sleep Disorder in Patients with Overactive Bladder

Abstract: Objective: To evaluate the efficacy of imidafenacin on nocturia and sleep disorder in patients with overactive bladder (OAB). Patients and Methods: A prospective multicenter study of imidafenacin 0.1 mg twice daily for patients with OAB and nocturia was conducted. At baseline and at week 4 and 8, patients were assessed using the overactive bladder symptom score (OABSS), frequency volume charts (FVC) and the Pittsburgh Sleep Quality Index (PSQI). Results: Treatment with imidafenacin significantly improved OAB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Moreover, HRQOL was improved according to the SF-8 (PCS and MCS), which revealed either significant improvement or a tendency for improvement from 8 weeks. Similar findings have recently been reported by Nagaoka et al [26] and Wada et al [27], who concluded that imidafenacin can be useful for the treatment of nocturia, sleep disturbance, and HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HRQOL was improved according to the SF-8 (PCS and MCS), which revealed either significant improvement or a tendency for improvement from 8 weeks. Similar findings have recently been reported by Nagaoka et al [26] and Wada et al [27], who concluded that imidafenacin can be useful for the treatment of nocturia, sleep disturbance, and HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Furthermore, OABSS is useful for determining the effect of treatment on urinary disorders. [89] In this study, we investigated the effect of pumpkin seed oil from C. maxima by OABSS. The OABSS was remarkably reduced in subjects given pumpkin seed oil extracted from C. maxima .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both sleep disorders and nocturia-related quality of life were improved by imidafenacin in patients with OAB and nocturia. Wada et al further demonstrated that imidafenacin for 8 weeks improved the PSQI, especially subjective sleep quality, sleep latency, and daytime dysfunction, in 26 patients with sleep disorders at baseline 39. Interestingly, they observed that imidafenacin significantly reduced the nocturnal polyuria index from 0.48 ± 0.11 to 0.43 ± 0.14 ( P < 0.05) as a result of a significant decrease in nocturnal urine volume from 888 ± 286 mL to 795 ± 294 mL ( P < 0.05) in 40 patients with nocturnal polyuria, although the mechanism involved remains unknown.…”
Section: Other Short-term Japanese Studies Of Imidafenacinmentioning
confidence: 96%